PENGARUH INTELLECTUAL CAPITAL TERHADAP KINERJA KEUANGAN - agasa, Qaharuna; Muharam, Harjum (JURNAL BISNIS STRATEGI, 2016)
This study has the main purpose to test the effect of the components of intellectual capital (VAICTM), namely CEE (Capital Employed Efficiency) HCE (Human Capital Efficiency), SCE (Structural Capital efficieny) on financial performance projected by ROA (Return on Assets), ROE (Return on Equity), ATO (Assets Turnover), and GR (Growth Rate) in non-financial companies listed on the Indonesian Stock Exchange (BEI) in the period 2012-2014.This research was conducted by using Partial Least Square (PLS) for data analysing. The research sample are 82 non-financial companies listed in the Indonesia Stock Exchange in 2012-2014. The requirements are companies with stable profit in 3 years, have enough component for calculating Value Added (VA), and have IDR (Rupiah) as the currency for financial report.The findings of this study is to indicate that there is a positive effect of intellectual capital components (VAICTM) on the financial performance of the company. Components of IC (VAICTM) also affect future financial performance. Overall, the empirical findings of this study stated that CEE (Capital Employed Efficiency) and SCE (Structural Capital efficieny) is a significant indicator for VAICTM on financial performance in the same year, CEE is a significant indicator of financial performance in the future. Limitations of this study is the use of all non-financial companies which qualify the needs assessment value added (value added) for 3 consecutive years - participated.